2017
DOI: 10.1017/jfm.2016.843
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of oscillating-grid turbulence interacting with a solid boundary

Abstract: Abstract:The interaction between oscillating-grid turbulence and a solid, impermeable boundary (positioned below, and aligned parallel to the grid) is studied experimentally. Instantaneous velocity measurements, obtained using two-dimensional particle imaging velocimetry in the vertical plane through the centre of the (horizontal) grid, are used to study the effect of the boundary on the rms velocity components, the vertical flux of turbulent kinetic energy (TKE), and the terms in the Reynolds stress transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 32 publications
(200 reference statements)
16
51
0
Order By: Relevance
“…In light of its statistical properties, oscillating-grid turbulence (OGT) has also been used to study the interaction of approximately zero-mean-shear turbulence at a boundary. In these studies u has typically been found to be amplified in the boundary-affected region 6,7,14,15 in qualitative agreement with the RDT predictions. 2,8 However, in a recent study 7 the current authors presented measurements of the terms of transport equation of TKE, which attributed the observed increase in u 2 primarily to the effects of turbulent transport, rather than intercomponent energy transfer.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…In light of its statistical properties, oscillating-grid turbulence (OGT) has also been used to study the interaction of approximately zero-mean-shear turbulence at a boundary. In these studies u has typically been found to be amplified in the boundary-affected region 6,7,14,15 in qualitative agreement with the RDT predictions. 2,8 However, in a recent study 7 the current authors presented measurements of the terms of transport equation of TKE, which attributed the observed increase in u 2 primarily to the effects of turbulent transport, rather than intercomponent energy transfer.…”
Section: Introductionsupporting
confidence: 72%
“…However, the subsequent development of the flow and its structure in studies in which a statistically stationary state is reached remains unclear. Results from a range of experimental and simulation based studies, conducted in both otherwise homogeneous 3,5 and inhomogeneous turbulence, 6,7 indicate that w remains inhibited by the boundary in accordance with the RDT proposed by Hunt and Graham 2 . However, controversy has arisen regarding whether the blocking of w continues to give rise to an intercomponent energy transfer from w 2 to u 2 through a correlation between the fluctuating pressure and velocity-strain fields, described by the so-called pressure-strain term Π s ij of the Reynolds stress transport equations.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In order to study thoroughly the part turbulence plays in the erosion process, we used a well-known experimental device that is the oscillating grid 7,8 . The flow produced by this device has been widely studied 1,7,[9][10][11][12] . All different studies agree in that far enough from the grid, the mean flow becomes weak enough to be negligible while turbulence appears to be almost isotropic.…”
Section: Introductionmentioning
confidence: 99%